Optimalisasi Pengembangan Usaha Kuliner Cheese Roll Sebagai Bentuk Kewirausahaan Kreatif di Sektor Makanan Ringan - Moh Afrizal Miradji; Anggini Lefteuw; Nayla Candyasari; Novita Boymau; Agustina Viviliani Burhan; Inna Fauziatun Nisa (Journal of Economic and Business Advancement, 2026)
This study aims to analyze the optimization of cheese roll culinary business development as a form of creative entrepreneurship in the snack food sector. The growing demand for innovative and practical food products has created significant opportunities for small-scale culinary businesses to develop sustainably. Creative entrepreneurship plays a crucial role in enhancing product innovation, marketing strategies, and business management to maintain competitiveness in a dynamic market environment. This research adopts a qualitative descriptive approach by examining entrepreneurial practices, innovation strategies, and market orientation in cheese roll businesses. The findings indicate that creativity in product variation, attractive packaging, and digital-based marketing significantly influences consumer interest and business sustainability. Furthermore, entrepreneurial knowledge and adaptive management contribute to the ability of businesses to respond to market changes and competition. The development of cheese roll businesses not only supports income generation but also strengthens the role of micro and small enterprises in the creative economy. Therefore, optimizing creative entrepreneurship is essential to ensure the long-term growth and resilience of culinary businesses in the snack food sector.